2022
DOI: 10.15366/reice2023.21.1.005
|View full text |Cite
|
Sign up to set email alerts
|

Segregación Escolar por Nivel Socioeconómico en Educación Primaria en América Latina y el Caribe

Abstract: Esta investigación tiene un doble objetivo: por un lado, estimar la magnitud de la segregación escolar por nivel socioeconómico en educación primaria en los países de América Latina y el Caribe y, por otro, contextualizar dichos resultados en el ámbito internacional. Para ello, se realiza una explotación de los microdatos del ERCE 2019, impulsado por la UNESCO/OREALC. La muestra final la componen 157.115 estudiantes de 7.214 escuelas escolarizados en 16 países de América Latina y el Caribe. Para estimar la seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
5
0
3
Order By: Relevance
“…Los futuros especialistas, bajo esta cultura performativa, optan por una equidad neoliberal en la conceptualización de la educación inclusiva. Se posicionan por una igualdad de oportunidades que termina responsabilizando al alumno/a del fracaso del sistema (Murillo y Martínez-Garrido, 2020). Estas cuestiones evidencian la importancia de cambios en la formación inicial hacia su consideración como un espacio desde el que ofrecer a las y los docentes en formación la oportunidad de cuestionar críticamente la influencia neoliberal en: (i) la finalidad de la educación y los valores que le dan forma, y (ii) la identidad o rol del especialista a la hora de contribuir a mantener y reproducir este "sentido común" (Gramsci, 1971).…”
Section: Discussionunclassified
“…Los futuros especialistas, bajo esta cultura performativa, optan por una equidad neoliberal en la conceptualización de la educación inclusiva. Se posicionan por una igualdad de oportunidades que termina responsabilizando al alumno/a del fracaso del sistema (Murillo y Martínez-Garrido, 2020). Estas cuestiones evidencian la importancia de cambios en la formación inicial hacia su consideración como un espacio desde el que ofrecer a las y los docentes en formación la oportunidad de cuestionar críticamente la influencia neoliberal en: (i) la finalidad de la educación y los valores que le dan forma, y (ii) la identidad o rol del especialista a la hora de contribuir a mantener y reproducir este "sentido común" (Gramsci, 1971).…”
Section: Discussionunclassified
“…In this sense, cultural gender stereotypes are relevant to consider, since they may be at the basis of the higher means obtained by boys compared to girls in terms of their mathematics self-concept [44]. Taking into account the socioeconomic segregation that Chile and Latin America generally experience [6,7], which has a detrimental impact on academic performance on standardized tests [1][2][3][4][5], the situation becomes more complex, preventing boys, and especially girls, from reaching their full potential and lowering family expectations [6,[8][9][10][11][12][13]. Consequently, it is important to make families and teachers aware of the issue so they can offer support and positive reinforcement to change this situation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the link between students' personal and social characteristics and academic performance, as noted in the standardized test scores in Chile and other Latin American countries [1][2][3][4][5]. This region has the highest segregation by socio-economic level [6], which affects students' academic development. It also negatively impacts teachers and students' families, linking with the families' low expectations [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, there has recently been an increase in interest in its assessment, particularly at a time when schools are dealing with complex circumstances that make it difficult for them to achieve their goals ( Guangbao and Timothy, 2021 ). In the case of Chile, there is a structural problem posed by high socioeconomic-based segregation, which has affected students’ development of different skills and academic performance and has also affected their families ( Murillo and Garrido, 2017 ; Murillo et al, 2018 , 2023 ; Salvo-Garrido et al, 2020 ). As a result, the work of teachers has been hampered and, therefore, challenged; even more so if the management of favorable learning environments depends largely on the talent and self-efficacy of the teachers ( Bandura, 1995 ).…”
Section: Introductionmentioning
confidence: 99%